STABILITY ANALYSIS AND ESTIMATION SOME GENETIC PARAAMETERS FOR GRAIN YIELD AND ITS COMPONENTS FOR SOME DURUM WHEAT GENOTYPES. - Hussain, M. A.; Sadeeq, M. AB.; Hassan, S. Y. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
Four durum wheat genotypes exotic from ICARDA and local variety were sown in agricultural season of 2015-2016, 2016-2017, and 2017-2018, using Randomized Complete Block Design (RCBD) with three replications. The result of the combined analysis of variance exhibited that the mean square of environments, genotypes and to evaluate their stability for genotypes x environment interaction (G X E) were significant for all traits, suggesting differential response of genotypes due to environment. When by partitioning G X E interaction in to the linear and non-linear (pooled deviation) components, that differences between environments (environment linear) were highly significant for all traits. For the GXE interaction linear, the results indicated that all traits were not significant except 1000-grain weight, The result also indicated that the durum wheat genotypes produced homogeneity for the most studied traits and much variation was noted in plant height and days to maturity. The genotype Miki-3 was superior in hectoliter and plant height and grain yield which gave 84.88 kgL/1000 87 and 2.37 T/ha respectively. The results exhibited that the phenotypic variation was more than the genotypic variation indicating that, the characters more affected by environments. For heritability in broad sense, the results showed moderate value for plant height and days to flowering and low for the rest traits. The genetic advance as the mean was low for all traits with the values ranged between 1.20 to 7.52 for hectoliter and 1000-grain weight. The lowest differences in genotypic and phenotypic coefficient of variability in the three seasons, this indicated that large amount of variation was contributed by environmental influence and low by genetic components. For stability analysis, the results indicated that the genotypes Miki3 and Simeto gave the best stability according to all parameters of stability with other genotypes and these genotypes gave highest value of grain yield 2.37 and 2.18.